Parental involvement in the Philippines: A review of literatures - Bartolome, Melissa T.; Mamat, Nordin; Masnan, Abdul Halim (Southeast Asia Early Childhood Journal, 2017)
Parental involvement refers to the amount of participation a parent has when it comes to the schooling of his/her children. Some schools foster healthy parental involvement, but sometimes parents has hesitations if they will involve themselves with their children’s education. It has been advocated in Western countries. However, there is a body of literature that examines the significance of social and cultural influences and the effects of parents’ involvement in and expectations of their children’s development and learning. It is important for schools to recognize the existence of cultural variations in parent involvement because there are differences among parents with diverse background on when, why, and how they are involved in their children’s education. Parenting is important in the Philippine society because family is viewed as a center to one’s social world. But, social contexts in which Filipino families are embedded have changed rapidly over the past ten years (Ochoa & Torre, n.d.). Children’s learning is increasingly moving toward a broader vision of the 21st century learning. As children’s educations increasingly occur across a range of settings, parents are uniquely positioned to help ensure that these settings best support their children’s specific learning needs. Thus, parental involvement researches remain misrepresentative of parents and the involvement that they have with their children’s education (Jackson, 2010).The present study is using a qualitative research design that will investigate existing literatures on parental involvement in Early Childhood Education in terms of communicating from the school, volunteering and participating in school’s activities, and learning at home. The study will rely on the analysis of documents in order to gain deeper understanding about parental involvement in the Philippines and propose a School-facilitated Parental Involvement (SPIn) Framework.